Sustainable development of on-shore wind power : integrated landscape character assessment as a tool to improve assessment of on-shore wind power in southern Sweden - Mascareño Suarez, Diego (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2022)
To meet the increasing demand of renewable energy and move from the fossil-fuel economy, Sweden aims to expand the onshore wind power production from 30 TWh today, to 80 TWh by 2040, with a strong expansion in Southern Sweden aiming to complement the infrastructure implemented in Northern Sweden. The implementation in Southern Sweden has created growing conflict as landscapes of cultural, ecological, and social importance try to accommodate this new energy landscape. The citizenry has also been affected, with their role or lack of it being crucial to the development of wind power in the South of Sweden. The aim of my analysis is to estimate the increase in these overlapping goals and how processes that improve decision-making at regional level and citizen participation can be crucial to the successful implementation of wind power in Southern Sweden. This aim will be mainly achieved through the answering of 4 main research questions: 1) estimate land ownership and land cover types in present and proposed onshore wind power developments Southern Sweden 2) How do present and approved wind power developments relate to National Interest areas in the southern counties of Skåne. Halland, Kronoberg and Jönköping? 3)How do present and approved wind power developments relate to National Interest areas in the southern municipalities of Falkenberg and Uppvidinge? 4) Have ILCA and similar assessments had an influence on successful Wind Power development implementation and Landscape Democracy in Falkenberg and Uppvidinge? All spatial analyses were carried out with a Geographical Information System. My results showed an increase up to 50% in impacted Arable Land in nemoral regions of Sweden and 94% in Conifer forests in boreonemoral regions of Sweden, with these land covers being the most relevant in each respective region. Private landowners are also shown to bear the brunt of the impacted areas, with an increase of 124% and 194% in nemoral and boreonemoral regions, respectively. Wind Power sites were found to visually impact ...